2022
DOI: 10.3389/feduc.2022.866519
|View full text |Cite
|
Sign up to set email alerts
|

The Reported Effects of the Pandemic on the Academic and Developmental Progress of Pupils in Specialist Provisions in England. Using Estimates From School and College Leaders to Determine Differences Between Economically Disadvantaged and Non-economically Disadvantaged Pupils With Special Educational Needs

Abstract: This paper addresses an identified gap in research during the COVID-19 pandemic: how the disruption impacted on pupils with special educational needs and disabilities (SEND) attending specialist (i.e., non-mainstream) settings in England. Estimates provided by around 200 special school and college leaders at two timepoints during the pandemic are used to provide overall estimates of the extent to which the pandemic and time spent out of school had on the academic and developmental progress of pupils in these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…There is limited evidence on the impact of school closures on the academic attainment of pupils with SENDs; early data indicates similar or greater learning loss compared to peers in the UK context (EEF, 2022; Webster et al, 2022). The reduction in supports impacted engagement in lessons and perceived academic progress for some autistic pupils in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited evidence on the impact of school closures on the academic attainment of pupils with SENDs; early data indicates similar or greater learning loss compared to peers in the UK context (EEF, 2022; Webster et al, 2022). The reduction in supports impacted engagement in lessons and perceived academic progress for some autistic pupils in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Existing survey research indicates that autistic youth experienced disproportionately high levels of anxiety during national lockdowns, without the decrease over time described in other populations. Toseeb and Asbury (2021) suggest that one explanation for this pattern is that “the source of the anxiety changed” (p.17) over the course of the pandemic. This idea is supported in our data.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of implications of the findings, clear direction in the face of future school closures or public health‐related emergencies is challenging to identify. COVID‐19 school closure research based on models of disease spread as well as impacts on developmental outcome such as social well‐being continues to emerge (e.g., Ashworth et al, 2023; Loades et al, 2020; Paterson et al, 2024; Webster et al, 2022). While few conclusions can yet be drawn regarding the risk and benefits of closing schools should similar events occur in the future, most agree that “Interventions that are particularly harmful to certain groups, such as school closures are on children, should be de‐emphasized and time limited” (Branch‐Elliman et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of implications of the findings, clear direction in the face of future school closures or public health-related emergencies is challenging to identify. COVID-19 school closure research based on models of disease spread as well as impacts on developmental outcome such as social well-being continues to emerge (e.g., Ashworth et al, 2023;Loades et al, 2020;Paterson et al, 2024;Webster et al, 2022) -Bastien et al, 2022;Trott et al, 2022). These outcomes are likely highly dependent on the individual child and their unique needs and experiences in using these devices to connect with peers.…”
Section: Mixed Findingsmentioning
confidence: 99%
“…If concluding this on the basis of the results of the present study were not enough, consider the compounding effects of the Covid pandemic. An investigation of special education during lockdown found that pupils who attended special schools experienced not only greater absence, learning loss and developmental losses, 6 compared with pupils in mainstream schools, but also disruption to -and in some cases, denial of -essential health, therapy and care services (Webster et al, 2022). If this is even part way indicative of what pupils with high-level SEND in mainstream schools experienced during the pandemic, the case for far-reaching reform ought to be as urgent as it is inevitable.…”
Section: Improving Teachers' Confidence and Competence With Sendmentioning
confidence: 99%